2006
DOI: 10.1016/j.bbabio.2006.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of free fatty acids with mitochondria: Coupling, uncoupling and permeability transition

Abstract: Long chain free fatty acids (FFA) exert, according to their actual concentration, different effects on the energy conserving system of mitochondria. Sub-micromolar concentrations of arachidonic acid (AA) rescue DeltapH-dependent depression of the proton pumping activity of the bc1 complex. This effect appears to be due to a direct interaction of AA with the proton-input mouth of the pump. At micromolar concentrations FFA increase the proton conductance of the inner membrane acting as protonophores. FFA can act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(100 citation statements)
references
References 68 publications
3
93
0
4
Order By: Relevance
“…SFR mitochondria exhibited increased ROS generation despite simultaneously overexpressing UCP2. Although the function of UCP2 is still unclear, it has been linked to the accumulation of FFAs in hepatocytes and muscle cells (12,46) and to mitochondrial ROS production (43). The mild uncoupling mediated by UCP2 may accelerate respiration rates and reduce the generation of ROS.…”
Section: Discussionmentioning
confidence: 99%
“…SFR mitochondria exhibited increased ROS generation despite simultaneously overexpressing UCP2. Although the function of UCP2 is still unclear, it has been linked to the accumulation of FFAs in hepatocytes and muscle cells (12,46) and to mitochondrial ROS production (43). The mild uncoupling mediated by UCP2 may accelerate respiration rates and reduce the generation of ROS.…”
Section: Discussionmentioning
confidence: 99%
“…One possible mechanism is that Dimebon may act as an anti-uncoupling agent decreasing proton leakage over the inner membrane, resulting in enhanced ∆ιm and ATP production. An example of a known anti-uncoupling agent is albumin, which binds natural uncouplers like free fatty acids [48]. In a study by Ward and colleagues, it was shown that hyperpolarization of ∆ιm is associated with increased glucose uptake, NADPH availability, ATP levels, and survival responses during excitotoxic injury.…”
Section: Discussionmentioning
confidence: 99%
“…Lipotoxic effects of free fatty acids have been suggested to be a key factor in development and also progression of hepatic steatosis (de Almeida et al, 2002;Malhi et al, 2006). In general, the term lipotoxic effects summarizes a potpourri of alterations in cellular metabolism observed in vitro upon addition of free fatty acids to cell cultures and includes 1) activation of stress-related signaling of JNK, 2) elevated expression of proinflammatory cytokines, 3) inhibition of mitochondrial ␀-oxidation, 4) elevated production of ROS, as well as enhanced generation of 5) toxic lipid intermediates and 6) lipid derivatives involved in altered cell signaling (Shimabukuro et al, 1998;Reddy, 2001;Borradaile et al, 2006b;Di Paola and Lorusso, 2006;Malhi et al, 2006). Saturated FA (i.e., palmitate) are the primary and most potent elicitors of lipotoxic effects (Eitel et al, 2002;Maedler et al, 2003;Weigert et al, 2004).…”
Section: Roles For Saturated and Monounsaturated Fatty Acids In Nonalmentioning
confidence: 99%